2022
DOI: 10.3389/fnut.2022.989090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixture design approach on nutritional characteristics and sensory evaluation of steamed bread added rice flour

Abstract: This study was designed to evaluate the effects of different rice nutrient compounds on steamed bread’s nutritional characteristics and sensory evaluation. The mixture design approach was used to research the interactions between different rice flours and wheat flours on the sensory evaluation of steamed bread. The arginine content of different rice flour (long-grained rice, polished round-grained rice, and black rice) was higher at 44.19, 21.74, and 34.78% than that of the common wheat, respectively. When the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Wheat flour cookies with 8% and 12% mulberry leaf additive had the significantly highest amount of this compound, while rice cookies without mulberry leaf additive had the significantly lowest amount. Wheat flour is a high-protein food that contains more protein than white rice [ 44 ]. Tian et al [ 44 ] reported that the protein content of different rice flours was 27.24–43.04% lower than that of common wheat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat flour cookies with 8% and 12% mulberry leaf additive had the significantly highest amount of this compound, while rice cookies without mulberry leaf additive had the significantly lowest amount. Wheat flour is a high-protein food that contains more protein than white rice [ 44 ]. Tian et al [ 44 ] reported that the protein content of different rice flours was 27.24–43.04% lower than that of common wheat.…”
Section: Resultsmentioning
confidence: 99%
“…Wheat flour is a high-protein food that contains more protein than white rice [ 44 ]. Tian et al [ 44 ] reported that the protein content of different rice flours was 27.24–43.04% lower than that of common wheat. Mulberry leaf powder is also high in protein, with levels ranging from 18.41 to 24.63% depending on genotypes [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there is limited awareness of the nutritional contents, financial feasibility, and profitability associated with Ube production (Hussin et al, 2020). Extensive research on the nutritional composition and economic viability of Ube production is lacking (Ge et al, 2022;Tian, Wei, & Chen, 2022), and strategies to maximize profitability in this market segment have not been well investigated (Meenu et al, 2023). These gaps hinder well-informed decision-making and the optimization of economic and nutritional advantages of Ube.…”
Section: Introductionmentioning
confidence: 99%